2022
DOI: 10.1002/cssc.202200916
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Hydrogenation of Squalene Using Parts per Million Levels of Palladium Supported on Carbon Nanotubes: Shift from Batch Reactor to Continuous‐Flow System

Abstract: The transition from batch catalytic processes to continuous flow processes requires highly active and stable catalysts that still need to be developed. The preparation and characterization of catalysts where palladium single atoms and nanoparticles are simultaneously present on carbon nanotubes were recently reported by us. These catalysts are considerably more active than commercial or previously described catalysts for the liquid phase hydrogenation of terpenes. Herein is shown that under solvent-free condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Finally, catC and catD were wash‐coated on metallic open‐cell solid foam structures to operate these catalysts in continuous flow mode. Such a “batch to continuous” transposition contributes to evaluate their stability, but also deserves an interesting demonstration for alternative reactor operation with these catalysts [36b,c] . Optical photographs (Figure S23) and SEM analysis (Figure S24) confirm a relatively uniform coverage of the structures, with an average catalyst layer thickness of 10–15 μm, in good agreement with the theoretical estimations based on weighing.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Finally, catC and catD were wash‐coated on metallic open‐cell solid foam structures to operate these catalysts in continuous flow mode. Such a “batch to continuous” transposition contributes to evaluate their stability, but also deserves an interesting demonstration for alternative reactor operation with these catalysts [36b,c] . Optical photographs (Figure S23) and SEM analysis (Figure S24) confirm a relatively uniform coverage of the structures, with an average catalyst layer thickness of 10–15 μm, in good agreement with the theoretical estimations based on weighing.…”
Section: Resultssupporting
confidence: 74%
“…Then, the cleaned substrates were activated thermally (5 °C min −1 , 4 h plateau at 600 °C, natural cooling down to ambient temperature) under air atmosphere. The activated foam pieces were then dip‐coated with a water suspension (60 g L −1 ) of the Pd/CNT catalyst following an already described procedure adapted from our previous works [36b,38] . The excess suspension was removed by air blowing through the coated structures.…”
Section: Methodsmentioning
confidence: 99%
“…S4e). The DFT models have been used in ARTEMIS 32 to generate FEFF paths to be compared with the experimental EXAFS data as shown in Fig. S5.…”
Section: Resultsmentioning
confidence: 99%
“…In the continuation of our studies on the cooperative catalysis between metal SAs and NPs [23,[29][30][31][32] herein, the catalytic performance of a RuSA/CNT catalyst (CNT: carbon nanotubes) for CAL hydrogenation in apolar solvent is first evaluated in order to produce HCAL. [4] Then, the catalytic performances of this catalyst were compared compared to the ones of RuSA-MNP/CNT catalysts (M = Ru, Pd, Ni) that can follow different pathways (B, C and/or D).…”
Section: Scheme 1 Different Pathways For H-spillover Induced Cooperat...mentioning
confidence: 99%
“…We have shown that controlling the ratio between PdSA and PdNP on carbon supports enables the design of very active hydrogenation catalysts integrating the ultra-rational use of precious metals [12][13][14]. These new catalysts may meet the need to increase catalytic activity for highly demanding substrates and conditions, like the solvent-free total hydrogenation of bio-based squalene (SQE) into squalane (SQA) (Scheme 1) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%